Analisis Pengaruh Pemberian Pakan Komersil Yang Difermentasi Terhadap Pertumbuhan dan Sintasan Ikan Nila (Oreochromis niloticus) - Agus Suryahman; Khairun Nisaa; Adam Asgar (Universitas Mataram, 2024)
The use of antibiotics can be used to kill harmful microorganisms, but uncontrolled use will have a negative effect on the body's defense system and the balance of important microorganisms and often give rise to more virulent pathogenic strains (Tumbol & Undap, 2016). One of the alternative efforts that can be made to increase the growth of tilapia is by adding probiotics to feed. Therefore, recent developments in cultivation businesses have developed the use of probiotics as a solution to abandon the use of chemicals and antibiotics. Because the use of probiotics in cultivation can maintain microbial balance and control phatogens in the digestive tract (Mansur & Tangko, 2008). Probiotics are living microorganisms that are very beneficial for living creatures, one of which is fish. The microorganisms contained in probiotics are able to help the digestion of food in the bodies of animals and humans so that food containing probiotics will be able to be digested and absorbed by the body properly. This research method is a description method using tables and graphs and the data obtained is analyzed using statistical tests to see real differences. The results of the research show that the addition of probiotics and molasses can have a significant effect on growth where the probiotics are completely absorbed in the feed so that they can improve the performance of the microflora in the digestive tract and help the food digestion process and stimulate increased nutrient absorption to support fish growth, while the treatment of providing probiotics and molasses in Feed did not have a significant effect on tilapia survival. After Tukey's test, it was discovered that there was no significant difference between treatments and tilapia survival during the study.